Multi‐century drought variability in the southern Min Mountains. (5th December 2019) - Yan, Xiaoya; Deng, Yang; Fan, Haowen; Su, Jiajia; Gao, Linlin; Gou, Xiaohua
Abstract: Information on moisture variability is important for climate adaptation and planning, which is urgently needed for the Jiuzhaigou County after it was hit by a magnitude 7.0 earthquake in August 2017, resulting in potential interactions between the earth surface processes and the hydroclimate. To study the regional hydroclimatic history beyond instrumental records, the first tree‐ring hydroclimate reconstruction, based on Pinus tabuliformis, was conducted in the southern Min Mountains, which is situated close to the areas affected by the Jiuzhaigou earthquake. The reconstruction, spanning from 1684 to 2017, explained 59% of the variance for May–August standardized precipitation evapotranspiration index at a 12‐month scale during 1962–2017. The recent drought, which occurred from 1992 to 2017 was the longest in duration, largest in magnitude, and had the second highest intensity. The most severe single year drought occurred in 1824, which was lower than the long‐term mean by 4 σ and affected several regions in and around the Northeast Qinghai‐Tibet Plateau. The drought reconstruction was consistent with other moisture reconstructions, but dissimilar were also exist during some periods. There was a significant correlation between drought reconstruction and sea surface temperature over many oceans. However, the correlations were unstable over time. This study suggests the importance of developing a density tree‐ring network to identify the spatial and temporal drought variability, as well as long‐term record for understanding regional climate dynamics. Abstract : Based on the first drought sensitive tree‐ring chronology developed in the southern Min Mountains, the drought variability since 1684 CE was reconstructed. According to the reconstruction, the recent persist drought is unprecedented over the past several centuries. A severe drought that influenced the Northeast Qinghai‐Tibet Plateau and around occurred at 1824 CE. Ocean forcing on regional drought variation is unstable over time.